Forging a Good Unilateral Contract or a Series of Good Contracts out of a Bad Bilateral Contract - John D. Calamari (Washington University Law Quarterly, 1961)
The title of this article is suggested by an article written by the late Dean Finn, then Professor Finn, in the Brooklyn Law Review. In that article Dean Finn urged, “Let us forge good unilaterals out of bad bilaterals if conscience points the way.” That article did not attempt to formulate rules which would help determine when the forging should occur. Professor Williston comes little closer to the formulation of a rule when he states: “An insufficient bilateral agreement may sometimes by performance on one side become a valid unilateral contract.” The purpose of this Article is to explore some of the problems concealed in Williston’s use of the word “sometimes” and to set forth some general rules which should apply to any phase of this problem. It will also examine the related problem of forging a series of good contracts out of a bad bilateral contract.
Keywords: Contracts